Potential economic benefits of carbon dioxide (CO₂) reduction due to renewable energy and electrolytic hydrogen fuel deployment under current and long term forecasting of the Social Carbon Cost (SCC) - Abdulla Rahil; Rupert Gammon; Neil Brown; Justin Udie; Muhammad Usman Mazhar (Energy Reports, 2019)
The 2016 Paris Agreement (UNFCCC Authors, 2015) is the latest of initiative to create an international consensus on action to reduce GHG emissions. However, the challenge of meeting its targets lies mainly in the intimate relationship between GHG emissions and energy production, which in turn links to industry and economic growth. The Middle East and North African region (MENA), particularly those nations rich oil and gas (O&G) resources, depend on these as a main income source. Persuading the region to cut down on O&G production or reduce its GHG emissions is hugely challenging, as it is so vital to its economic strength. In this paper, an alternative option is established by creating an economic link between GHG emissions, measured as their CO2 equivalent (CO2e), and the earning of profits through the concept of Social Carbon Cost (SCC). The case study is a small coastal city in Libya where 6% of electricity is assumed to be generated from renewable sources. At times when renewable energy (RE) output exceeds the demand for power, the surplus is used for powering the production of hydrogen by electrolysis, thus storing the energy and creating an emission-free fuel. Two scenarios are tested based on short and long term SCCs. In the short term scenario, the amount of fossil fuel energy saved matches the renewable energy produced, which equates to the same amount of curtailed O&G production. The O&G-producing region can earn profits in two ways: (1) by cutting down CO2 emissions as a result of a reduction in O&G production and (2) by replacing an amount of fossil fuel with electrolytically-produced hydrogen which creates no CO2 emissions. In the short term scenario, the value of SCC saved is nearly 39% and in the long term scenario, this rose to 83%.
Keywords: C69; C80; L91; L94; P18; P48; Q55; 330; Central electrolyser; Economic benefits; Middle East and North Africa; Social carbon cost; Surplus renewable energy